2006
DOI: 10.1097/00131746-200605000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Suicide Attempts and Low-Lethal Self-Harm Behavior Among Psychiatric Inpatients

Abstract: In this study, we examined the relationship between suicide attempts and low-lethal self-harm behavior in a sample of psychiatric inpatients. Using a cross-sectional approach, we surveyed 107 participants about their histories of suicide attempts, including overdoses, as well as various low-lethal self-harm behaviors. Compared with those without such histories, individuals with histories of suicide attempts, including overdoses, were significantly more likely to report a greater number of: 1) low-lethal self-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Safer [2] reviewed the literature relating to adolescent populations and concluded that there was no convincing overlap between suicide attempts and "deliberate self-harm." In a study of 107 psychiatric inpatients, we confirmed a relationship between a history of suicide attempts and a number of low-lethal selfharm behaviors [3], including a symptom cluster of three medically self-defeating behaviors-that is, the prevention of wounds from healing, the abuse of prescription medications, and the purposeful exercising of an injury. Collectively, these sample studies report inconsistent results regarding whether patients with high-lethal behaviors, such as suicide attempts, engage in other forms of nonsuicidal self-destructive behavior.…”
mentioning
confidence: 59%
“…Safer [2] reviewed the literature relating to adolescent populations and concluded that there was no convincing overlap between suicide attempts and "deliberate self-harm." In a study of 107 psychiatric inpatients, we confirmed a relationship between a history of suicide attempts and a number of low-lethal selfharm behaviors [3], including a symptom cluster of three medically self-defeating behaviors-that is, the prevention of wounds from healing, the abuse of prescription medications, and the purposeful exercising of an injury. Collectively, these sample studies report inconsistent results regarding whether patients with high-lethal behaviors, such as suicide attempts, engage in other forms of nonsuicidal self-destructive behavior.…”
mentioning
confidence: 59%
“…2,3 Previous research has shown that NSSI is associated with numerous risk factors and correlates, including: SUDs, childhood sexual abuse, MDD, SA, and completed suicide. [4][5][6][7][8] Interestingly, several studies demonstrate an association between NSSI and suicidal behaviour. In a sample of offspring of parents with a DSM-IV mood disorder, Cox et al 5 found in multivariate models that a diagnosis of depression, greater aggression, depressive symptoms, and suicidal ideation were the strongest correlates of NSSI.…”
Section: Limitationsmentioning
confidence: 99%
“…Existing data strongly suggest that SA and suicidal ideation are common among people who engage in NSSI. 4,8,[14][15][16] Teasing apart the unique correlates and risk factors of NSSI and SA has major implications for clinical practice and public health initiatives. Bridging these gaps is important to better inform the study and treatment of self-harm behaviour.…”
Section: Limitationsmentioning
confidence: 99%
“…18 NO. 64 An audit revealed that approximately 20% of inmates are assigned to an ACCT in any given year. Other work has shown that up to one-quarter of women could self-harm during their current term.…”
Section: Initial Sample Size Calculationsmentioning
confidence: 99%
“…The internal consistency was not reported in the initial development work, but it has subsequently been reported as between 0.8 and 0.9. [62][63][64] Additionally, the SHI has been shown to satisfy the requirements of Rasch scaling assumptions among a non-clinical sample. 59 For the analysis, a total score was generated where < 10% of items were missing (i.e.…”
mentioning
confidence: 99%